Breast cancer, screening and diagnostic tools: All you need to know. (January 2021) - Barba, Diego; León-Sosa, Ariana; Lugo, Paulina; Suquillo, Daniela; Torres, Fernando; Surre, Frederic; Trojman, Lionel; Caicedo, Andrés
Graphical abstract: Highlights: Nearly two million cases of breast cancer are diagnosed each year worldwide. Multidisciplinary approaches are used to develop screening and diagnostic tools. Key information is provided on breast cancer for medical and research professionals. Breast cancer biology, standard and innovative detection tools are presented. This information is needed to develop better diagnostic and screening tools. Abstract: Breast cancer is one of the most frequent malignancies among women worldwide. Methods for screening and diagnosis allow health care professionals to provide personalized treatments that improve the outcome and survival. Scientists and physicians are working side-by-side to develop evidence-based guidelines and equipment to detect cancer earlier. However, the lack of comprehensive interdisciplinary information and understanding between biomedical, medical, and technology professionals makes innovation of new screening and diagnosis tools difficult. This critical review gathers, for the first time, information concerning normal breast and cancer biology, established and emerging methods for screening and diagnosis, staging and grading, molecular and genetic biomarkers. Our purpose is to address key interdisciplinary information about these methods for physicians and scientists. Only the multidisciplinary interaction and communication between scientists, health care professionals, technical experts and patients will lead to the development of better detection tools and methods for an improved screening and early diagnosis.